Climate-resilient zero energy buildings: Long-term modelling for energy efficiency and renewables impact - Nada Youssef Ahmed; Francisco Javier Rey Martínez; Javier M. Rey Hernández (Results in Engineering)
Amidst mounting concerns over global climate change, there is an urgent need to adapt to the built sector's significant contribution to greenhouse gas emissions. This study analyzes the performance of the INDUVA Near Zero Energy Building (nZEB) at the University of Valladolid, Spain, exploring how building dynamics interact with climate change scenarios for 2022, 2050, and 2080, which projects a 25 % decrease in heating consumption and a 100 % increase in cooling consumption by 2050. By 2080, heating consumption is expected to drop by 39 %, while cooling consumption may rise by 170 %. As a result, CO2 emissions are projected to increase by 10 % in 2050 and 14.5 % by 2080. Additionally, the study examines the impacts of relocating the non-residential nZEB to different climate regions, including Tropical, Arid, Continental, and Polar regions. Using DesignBuilder Version 7 and CCWeatherGen, it simulates energy consumption and CO2 emissions across various future weather files, reflecting diverse scenarios, which evaluates relocation scenarios to Juneau and Warsaw, revealing performance improvements in CO2 emissions with a decrease of 3.94 and 2.9 tons/year, respectively, in 2022 and a further reduction in 2050 and 2080. This study highlights the importance of adapting thermal insulation and material selection, especially when relocating to polar and continental climates by 2050 and 2080. Overall, this study explores the relocation of nZEBs in five climate regions, highlighting the interaction between design, climate, and energy performance. It emphasizes the necessity for region-specific solutions and renewable energy integration to enhance resilience and sustainability amid changing climate challenges.